An optimized protocol for quality control of gene therapy vectors using nanopore direct RNA sequencing - Zeglinski, Kathleen; Montellese, Christian; Ritchie, Matthew E.; Alhamdoosh, Monther; Vonarburg, Cédric; Bowden, Rory; Jordi, Monika; Gouil, Quentin; Aeschimann, Florian; Hsu, Arthur (Genome Research, 2024)
Despite recent advances made toward improving the efficacy of lentiviral gene therapies, a sizeable proportion of produced vector contains an incomplete and thus potentially nonfunctional RNA genome. This can undermine gene delivery by the lentivirus as well as increase manufacturing costs and must be improved to facilitate the widespread clinical implementation of lentiviral gene therapies. Here, we compare three long-read sequencing technologies for their ability to detect issues in vector design and determine nanopore direct RNA sequencing to be the most powerful. We show how this approach identifies and quantifies incomplete RNA caused by cryptic splicing and polyadenylation sites, including a potential cryptic polyadenylation site in the widely used Woodchuck Hepatitis Virus Posttranscriptional Regulatory Element (WPRE). Using artificial polyadenylation of the lentiviral RNA, we also identify multiple hairpin-associated truncations in the analyzed lentiviral vectors (LVs), which account for most of the detected RNA fragments. Finally, we show that these insights can be used for the optimization of LV design. In summary, nanopore direct RNA sequencing is a powerful tool for the quality control and optimization of LVs, which may help to improve lentivirus manufacturing and thus the development of higher quality lentiviral gene therapies.